2023
DOI: 10.3390/biom13061003
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Invasiveness of Endometriotic Cell Lines to Breast and Endometrial Cancer Cell Lines

Abstract: Endometriosis is an invasive condition that affects 10% of women (and people assigned as female at birth) worldwide. The purpose of this study was to characterize the relative invasiveness of three available endometriotic cell lines (EEC12Z, iEc-ESCs, tHESCs) to cancer cell lines (MDA-MB-231, SW1353 and EM-E6/E7/TERT) and assess whether the relative invasiveness was consistent across different invasion assays. All cell lines were subjected to transwell, spheroid drop, and spheroid-gel invasion assays, and stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…In addition, it is widely recognized that angiogenesis plays a crucial role in the formation and spread of EMs lesions to abnormal sites [27], and the main regulator of the angiogenic process is VEGF [28]. Meanwhile, EMs is an aggressive condition and E-cadherin expression could reflect its considerable invasiveness [29]. The high expression of PCNA and VEGF and the low expression of E-cadherin in endometrial tissues reported in this study suggests that EMs was successfully induced in rats.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, it is widely recognized that angiogenesis plays a crucial role in the formation and spread of EMs lesions to abnormal sites [27], and the main regulator of the angiogenic process is VEGF [28]. Meanwhile, EMs is an aggressive condition and E-cadherin expression could reflect its considerable invasiveness [29]. The high expression of PCNA and VEGF and the low expression of E-cadherin in endometrial tissues reported in this study suggests that EMs was successfully induced in rats.…”
Section: Discussionmentioning
confidence: 59%
“…Endometriosis is a benign disease, but it has some invasive and aggressive features and an immune microenvironment similar to malignancy [125]. For example, in a study of the treatment of triple-negative breast cancer, researchers found that tumor tissues had a different metabolic phenotype of ferroptosis from normal tissues through metabolomics, and inhibition of the key ferroptosis protein GPX4 could effectively enhance cellular antitumor immunity [68].…”
Section: Discussionmentioning
confidence: 99%